The effect of vitamin C in adults with sepsis: a meta-analysis of randomized controlled trials - Luo, Xing; Zhu, Youfeng; Zhang, Rui; Zhu, JianQiu; Kuang, Huanming; Shao, Yuebin; Guo, Xinmin; Ning, Bo (Frontiers in Medicine, 2023)
The effect of intravenous (IV) vitamin C in the treatment of sepsis remains controversial. We aimed to explore the clinical efficacy of vitamin C in the treatment of sepsis.: Electronic databases (PubMed, Embase, Web of Science, and Cochrane Library) were searched from inception through November 15th, 2022, for randomized controlled trials evaluating the effect of IV vitamin C treatment in patients with sepsis. The primary outcome was short-term mortality, secondary outcomes included duration of vasopressor use, length of intensive care unit (ICU) stay, and Sequential Organ Failure Assessment (SOFA) score after vitamin C treatment. Subgroup analyses were performed based on the dose and duration of IV vitamin C and region to determine whether vitamin C benefited patients with sepsis.Results: A total of 10 studies including 1426 patients fulfilled the predefined criteria and were analyzed. Overall, there were no significant differences between the vitamin C group and the control group regarding short-term mortality (odds ratio [OR], 0.61; 95% confidence interval [CI] 0.37-1.01; P=0.05), ICU length of stay (mean difference [MD], -1.24; 95% CI -3.54 to 1.05, P = 0.29) and SOFA score (MD, -0.85, 95% CI -2.38 to 0.67, P = 0.27). However, vitamin C significantly reduced the duration of vasopressor use (MD, −14.36, 95% CI −26.11 to −2.61, P=0.02). Furthermore, subgroup analysis found that in developing countries, vitamin C was associated with a significant reduction in short-term mortality (OR, 0.33; 95% CI 0.12-0.90; P=0.03), duration of vasopressor use (MD, -24.37, 95% CI -33.72 to -15.02, P <0.001) and SOFA score (MD, -2.55, 95% CI -4.81 to -0.28, P = 0.03).In our study, vitamin C administration for sepsis patients was not associated with a significant reduction in short-term mortality, length of ICU stay or SOFA score. However, we observed that vitamin C could reduce the duration of vasopressor use. Furthermore, sepsis patients in developing countries may benefit more from vitamin C administration than those in developed countries.